2020
DOI: 10.3390/cancers12040900
|View full text |Cite
|
Sign up to set email alerts
|

The n-10 Fatty Acids Family in the Lipidome of Human Prostatic Adenocarcinoma Cell Membranes and Extracellular Vesicles

Abstract: A new pathway leading to the n-10 fatty acid series has been recently evidenced, starting from sapienic acid, a monounsaturated fatty acid (MUFA) resulting from the transformation of palmitic acid by delta-6 desaturase. Sapienic acid has attracted attention as a novel marker of cancer cell plasticity. Here, we analyzed fatty acids, including the n-10 fatty acid contents, and for the first time, compared cell membranes and the corresponding extracellular vesicles (EV) of two human prostatic adenocarcinoma cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
0
24
0
1
Order By: Relevance
“…In the beginning, it was thought that exosomes were a fairly homogeneous class of extracellular vesicles, but more recent experimental pieces of evidence have highlighted the enormous diversity in the exosome category so as to define distinct subtypes released for example from the apical or basolateral surface of tumor cells [90]. The various subtypes of exosomes differ according to biogenesis [91], lipid composition [92], surface markers [93], and obviously for the cargo [94].…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning, it was thought that exosomes were a fairly homogeneous class of extracellular vesicles, but more recent experimental pieces of evidence have highlighted the enormous diversity in the exosome category so as to define distinct subtypes released for example from the apical or basolateral surface of tumor cells [90]. The various subtypes of exosomes differ according to biogenesis [91], lipid composition [92], surface markers [93], and obviously for the cargo [94].…”
Section: Discussionmentioning
confidence: 99%
“…The analytical approach for the unambiguous characterization and discrimination of positional and geometrical fatty acid isomers having the 16:1 structure is crucial for the determination of the sapienic acid presence. We described in detail the protocol of fatty acid analysis, which includes a crucial derivatization step to localize the double bond position, using the well-known dimethyl disulfide (DMDS) adducts and its diagnostic fragmentation in mass spectrometry [ 6 , 10 , 63 , 79 ]. It must be added that such derivatization procedure and mass spectra can be performed by regular equipment in chemical labs, and do not require specialized and expensive instrumentation.…”
Section: The Study Of the Cancer Lipidome And The Discovery Of mentioning
confidence: 99%
“…In the same study, the biophysical properties of the cell membranes were monitored by two-photon fluorescent microscopy, using Laurdan as a dye, showing that the supplementation of sapienic acid, with respect to its positional isomer palmitoleic acid, increased fluidity in several regions, evidently correlated with the formation and distribution of n-10 MUFA and PUFA in lipid domains. Following the interest in extracellular vesicles EVs (exosomes) as relevant sites for cancer metabolism and diagnostics [ 84 ], we investigated the presence of the n-10 fatty acid family, comparing membrane phospholipids and EVs of prostate cancer cell lines with different degrees of aggressiveness: PC3 (prostate cancer) and LNCaP (prostate derived from metastatic site: left supraclavicular lymph node), the former being more aggressive [ 10 ]. We found that 12–13% of the membrane fatty acids of these cell lines were composed of n-10 fatty acids, with the sapienic acid content >7%.…”
Section: The Study Of the Cancer Lipidome And The Discovery Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been shown that EVs released by tumor cells during malignant progression contain proteins [24], nucleic acids [25,26], and lipids [27] that can be used as markers of the neoplastic and metastatic phenotype. An example is the identification of caveolin-1, a protein associated with the metastatic behavior of tumors, in plasma EVs.…”
Section: Biological and Functional Features Of Evsmentioning
confidence: 99%